Action research of an error self-correction intervention: Examining the effects on the spelling accuracy behaviors of fifth-grade students identified as at-risk. Issue 2 (3rd April 2017) - Turner, Jill; Rafferty, Lisa A.; Sullivan, Ray; Blake, Amy
ABSTRACT: In this action research case study, the researchers used a multiple baseline across two student pairs design to investigate the effects of the error self-correction method on the spelling accuracy behaviors for four fifth-grade students who were identified as being at risk for learning disabilities. The dependent variable was the participants' spelling skills, which were measured using weekly spelling tests. The study took place in an integrated co-taught classroom, over a 15-week period with one spelling test per week. The results indicated that error self-correction was an effective intervention to improve the spelling accuracy behaviors of students at risk for learning disabilities. The participants' mean weekly spelling test scores improved at least 24% over baseline levels during the intervention phase. A discussion of the results and suggestions for implementation are included.